Hzarat Ismail (AS) - Karam , Ambia (Lahore , Karachi children's publications)
In Islam, Ishmael is regarded as a prophet (nabi) and an ancestor to Prophet Muhammad SAW. He also became associated with Mecca and the construction of the Kaaba, as well as equated with the term "Arab" by some.